Responces of identified cardioregulatory neurons within CNS of mollusc Lymnaea stagnalis at hyperglycemia and insulin action - Sidorov, Alexander V.; Shadenko, Victoria N.; Kazakevich, Victor B. (Experimental Biology and Biotechnology, 2019)
Increase in haemolymph glucose level (from 0,09 (0,08; 0,10) to 0,54 (0,44; 0,69) mmol/L) and intracavitary injection of insulin (0,05 IU/g) results in 10 –20 % growth of heart rate in comparison with control group. Multidirectional effects of glucose (10 mmol/L) and insulin (0,2 IU) – 1,6-time increase and 2,3-time decrease of firing rate respectively, were observed in identified peptide-containing neurons V.D.1 and R.Pa.D.2. Both these substances initiate the appearance of synaptic inputs on the membrane of the R.Pa.D.1 neuron, being the evidence of the central cardioregulatory rhythm activation within CNS of Lymnaea. It is assumed that shifts of glucose level are involved in neuronal cardioregulation in molluscs.